Variation in Anatomical and Secretory Structure of Annona Species has Potential as Medicinal Plant - Febriyani, Hanik; Pratiwi Puspitawati, Rinie; Bashri, Ahmad (LenteraBio : Berkala Ilmiah Biologi, 2022)
The Annona plant has a high content of secondary metabolites. Metabolites are removed from the secretory structure of this plant. This study aims to describe the anatomical and secretory structures of the three Annona species that have the potential to produce secondary metabolites. The research was conducted on the leaves of Annona muricata, Annona squamosa and Annona cherimola using paraffin and whole mount methods for transverse and paradermal observation of the preparations. The results of the research on the three Annona species showed the anatomical structures in the form of curved and grooved anticlinal epidermal walls, long sclereid cells, stone cells, parasitic stomata, the highest density in A. muricata (527,34/mm2) and the medium density in A.squamosa (454,89/mm2), the highest density index in A.cherimola (0,137), while trichomes in the form of glandular and non-glandular trichomes were only found in A. muricata and A. cherimola. Secretory structures that have potential as medical for anticancer, antitumour, hypertension, antibacteria, fungal infections and antidepressants were found in the form of essential oil cells in A. muricata species and lithic cells, idioblast cells, secretory spaces in these three Annona species. The secretory structures in thes three Annona species have variations in both cell types and locations.